1989
DOI: 10.1103/physrevb.39.202
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of lattice instabilities in YBa2Cu3

Abstract: We have performed a molecular dynamics simulation of the YBa2Cu3O.i structure under the constraints of the rigid-ion model. These simulations used a variety of charge states for the Cu ions and the 0 ions, and except for one case, the interionic potentials were obtained in an ab initio fashion. The results of these simulations showed that a lattice instability involving the Cu-0 chains existed. This instability was further investigated and it was shown that simple electronic screening is probably insufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the case of YBCO, our molecular dynamics simulations (Billesbach et al, 1989) indicate that the nominal structure (from X-ray and neutron measurements) (Capponi, et al, 1987;You et al, 1987;Marsh et al, 1988;Williams et al, 1988) can never be other than metastable. Specifically, the oxygen chains along the b axis are under compression due to the fact that barium-oxygen distances in the layers of square pyramids above and below are too short.…”
Section: I1 Basic Theorymentioning
confidence: 91%
“…In the case of YBCO, our molecular dynamics simulations (Billesbach et al, 1989) indicate that the nominal structure (from X-ray and neutron measurements) (Capponi, et al, 1987;You et al, 1987;Marsh et al, 1988;Williams et al, 1988) can never be other than metastable. Specifically, the oxygen chains along the b axis are under compression due to the fact that barium-oxygen distances in the layers of square pyramids above and below are too short.…”
Section: I1 Basic Theorymentioning
confidence: 91%
“…A conclusion of possible O͑1͒ destabilization in the 123 system with the formation of zigzag chains has been obtained based on molecular dynamics calculations also in Ref. 19.…”
mentioning
confidence: 87%
“…We use ionic model to simplify this problem. Some authors [2][3][4][5][6][7][8] have demonstrated that the ionic model can be used to deal with the high-temperature superconductors. According to Pauling's rule, 9 it is reasonable to consider that the Bi-system superconductors are ionic compounds.…”
Section: Modelmentioning
confidence: 99%